Zinc-mediated attenuation of salinity stress: a study on photosynthetic pigment stability, water balance, and yield of soybean (Bangladesh Journal of Botany, 2026)
An experiment was conducted in zinc-treated soil with 0, 50, 100, 150, 200, and 250 mM NaCl salinity to assess their interaction effect on photosynthetic pigment stability, water balance, and yield of soybean. Salinity reduced photosynthetic pigments, RWC, WRC, and exudation rate, while increasing WSD and WUC. Zinc application mitigated these effects by improving pigment levels, water relations, and yield attributes. Moderate salinity (150 mM NaCl) showed the highest response to Zn application in terms of physiological and yield improvements. Zinc also improved seed yield, pod characteristics, and branch number under salinity. These findings suggest that Zn treatment can partially attenuate the toxic effects of Na+ and Cl- ions and improve soybean yield by enhancing photosynthetic pigment levels and maintaining water status.Bangladesh J. Bot. 55(2): 295-301, 2026 (June)